Communication Strategy Of The Pepelingasih Program - Silvia Rahmawanti, Mada; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2022)
Pepelingasih program involving pioneer youths throughout the province that concentrates on environmental care, especially river cleanliness from piles of garbage. Pepelingasih as a government program certainly has many challenges, in addition to the lack of public awareness regarding waste as well as how to implement or implement other programs to have a positive impact. This study aims to determine the communication strategy of the Pepelingasih program in Sidoarjo Regency. The focus in this research is Implementation according to Edward III on communication in Pepelingasih, Sidoarjo Regency. This study used a qualitative descriptive research method. Data collection techniques are through observation, interviews and document analysis. The data analysis technique uses the Miles and Huberman model in Sugiyono (2014: 246), namely data collection, data reduction, data presentation, drawing conclusions. The result of this research is that communication in the transmission dimension has been going well in accordance with the applicable standard procedures and guidelines. The dimension of clarity in getting public information can be seen on the Disparbudpar and Pepelingasih Instagram, and you can also come directly to the Sidoarjo Regency Disparbudpar office by meeting the youth staff. The consistency dimension has provided consistent services and information based on Standard Operating Procedures.